Faktor Sanitasi Rumah serta Hubungannya dengan Kejadian Stunting di Kabupaten Banyumas - Agnes Fitria Widiyanto; Erna Kusuma Wati (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2022)
Stunting is a growth disorder that occurs due to chronic malnutrition or infectious diseases. The effects include slow child growth, low endurance, lack of intelligence and low productivity. Data analysis was performed to see the relationship between variables and risk magnitude (OR) using the Chi-square test or Fisher Exact if the requirements for the Chi-square test were not met with a 95% confidence level (α = 0.05). Stunting can cause a decline in public health conditions. Stunting problems can be done by cross-sectoral handling. Other issues such as children with LBW have a significant relationship with stunting. Health promotion can be done to deal with stunting. Stunting risk factors can occur due to environmental sanitation conditions in the home community. Home environmental sanitation that can cause stunting, among others, occurs due to the condition of the house floor, ceiling, latrines and the provision of clean water. There is a need for a government program to improve house sanitation conditions to prevent and eliminate stunting.